The Association between Firm-Specific Characteristics and Voluntary Disclosure of Listed Companies in Kuwait - Haneh, Abdullah Mohammed Abdullah (2009)

(untitled)
Many studies have examined the relationship between a company’s characteristics and the level of disclosure in both developed and developing countries that enjoyed political and economic stability. This study aims to examine the influence of some firm characteristics which include firm size, debt ratio, profitability, ownership dispersion, audit firm size,industry sector and year - and voluntary disclosure level of Kuwait companies. For the purpose of this study, 38 companies in the real estate and investment sector - forming approximately 17.4 percent of the total firms listed in Kuwait stock exchange are chosen from Kuwait stock exchange. Data are drawn from annual reports of these companies for a period of four years 2005, 2006, 2007 and 2008. By using correlation and regression analysis, the study found that, except firm size, profitability and industry sector, all variables are related positively and with disclosure level of Kuwait companies in the real estate and investment sector.